44 - HYDROCOLLOID PATCH AS A STRATEGY FOR PRESSURE ULCER PREVENTION: SEEKING EVIDENCE FOR NURSING (Fiep Bulletin - online, 2011)
Introduction: Pressure Ulcers (PUs) increase patient morbidity, mortality and hospitalization time, lowering life quality. The hydrocolloid patch, a self-adhesive device used in the treatment of these wounds, has been used as a preventive strategy in the reduction of friction and shearing forces. However, it's been observed this practice is based on the nurse's individual decision, with no scientific basis. Objectives: to identify in literatyre studies that cover the use of hydrocolloid patches as an effective device on the prevention of PUs. Method: bibliographical research on MEDLINE, LILACS, SciELO and Centro Cochrane do Brasil databases, by descriptors: Úlcera de Pressão, Prevenção, Curativos Hidrocolóides. The articles were analyzed regarding the study object, employed methodology, result analysis and clinical application. Results And Discussion: the selected studies present a consensus on the use of hydrocolloid patches as an assisting material in the reduction of friction and shearing forces. There is, however, not enough evidence strength to recommend its use, since the patches received C-grade recommendation in the systematic revision study. Conclusions: the use of hydrocolloid patches associated with other measures has been a strategy for PU prevention, however its effectiveness has been questioned given the low evidence in studies. It is thus necessary to proceed with randomized clinical studies so this practice can be based on the best available scientific evidence, with acceptable cost-benefit and accessible to any patient.
Keywords: Pressure Ulcer; Prevention; Hydrocolloid Patches